DIOPTASE - Cook R.B. (My University, 2002)
Describes the characteristic of dioptase. Description of the various bluish shades; Exhibition of cleavage and conchoidal to uneven fracture; Characterization as copper silicate hydroxide.
Keywords: COPPER SILICATES